Habilidades auditivas centrais em indivíduos com queixas de dificuldades escolares e sua relação com a vantagem da orelha direita em escuta dicótica - Palacios, Thilie [UNIFESP] (2017)
Propouse: such the association between central auditory skills and the presence or absence of the right ear advantage in dichotic hearing in individuals with schooler. Methodology: difficulties. The population of 121 individuals, public or private school in the city of São Paulo, with the control group (SQ) 52 children (29 public schools and 23 private schools) without learning difficulties and advantage of the right ear (VOD) study group 1 (CQ) 51 children (26 public schools and 25 private schools) with learning difficulties and VOD; and Study Group 2 (CQE) with 18 children, all public school with learning difficulties and lack of VODOs inclusion criteria: have at least elementary school (to be literate), has no other obvious impairments that hinder the development of language and / or speech, such as neurological and / or psychiatric disorders, and does not have serious visual disorders such as glaucoma and / or low vision. Process: To evaluate the detection of a sound in the presence of binaural auditory masking with a change of phase to one ear is used MLD test; to check the temporal resolution of behavior will use the GIN test; to check the temporal ordering behavior will be used TPD test; to check the monotic behavior with sentences will use the SSI-MCI test; to check the dichotic listening behavior syllables will be used TDCV test. Data for each procedure will be compared considering the variable group, presence and absence of school difficulties complaints, and presence and absence of the right ear advantage in dichotic hearing. Result: In subjects with central auditory processing disorder, the ability to release binaural masking was found to be lacking in association between the group and the adequacy reference coefficient, nor between gender and CR criteria of adequacy of performance in the test. For the temporal resolution ability the individuals of the CQ group showed worse performance than the SQ group. For the temporal ordering ability of successive, brief and different durations, it was observed that the group is associated with CR and not with gender. The difference between the means of the SQ and CQ groups is significant. For figure-background ability in monotonous listening with sentences, the data to the right ear were associated with the presence of a complaint of school difficulty rather than gender, while the left ear showed no interaction between gender or group. The ability of figure-background in dichotic listening with syllables was shown with association between group and CR. The amplitude of the right ear advantage, abbreviated as ILOD, was shown with interaction between group, gender and CR in the SQ group, but in the CQ group the same association was not observed, and a significant difference was also observed between the groups. Conclusion: There is impairment of central auditory skills in individuals with school difficulties. The amplitude of the advantage of the right ear is lower in the group with school difficulties.